Kansas grain supply response to economic and biophysical changes - Boussios, David (Kansas State University, 2012)
This research identifies and quantifies the impact of biophysical and economic variables on Kansas crop acreage and yields for the period 1977- 2007. Due to long production time requirements, agricultural producers must make vital decisions with imperfect information, based on expectations of future agronomic and economic conditions. This research analyzes the impact of price, climate, and yield expectations on crop acreage allocations and yield responses for the four major commodities produced in Kansas: corn, soybeans, wheat, and grain sorghum (milo). By modeling and analyzing both biophysical and economic variables, total supply response can be estimated for potential future changes in prices, yields, climate, and weather outcomes. The analysis of both biophysical and economic conditions allows for the estimation of supply response in the short and long run. The results provide updated, more precise results than previous research, which has often separated acreage and yield response.
Keywords: Agricultural supply; Kansas; Grain; Commodity; Acreage response; Yield response; Agriculture, General (0473); Economics (0501); Economics, Agricultural (0503)